The identifications and responses of Baby Boomers to social conflicts in the late 1960s and early 1970s reflected in James A. Michener’s “The drifters” = Những nhận dạng và hồi đáp của thế hệ Baby Boomer đối với những mâu thuẫn xã hội trong những năm cuối thập niên 60 và đầu thập niên 70 phản ánh trong tác phẩm “the drifters” của James A. Michener - Phạm, Ngọc Liên (2020)
After World War II, the Baby Boom in America brought the country one impressively unique generation, often known as the Baby Boomers. Due to the after-war Baby Boom, Baby Boomers came into the stage light of history with extravagant number; thus, they became the main force of changes in American society. In the late 1960s – early 1970s, with the first Baby Boomers growing out of their teens, ensured by the social wealth and stability and empowered by college education, emerged their first significant contributions to their society. Among which were the Antiwar Movement, the Civil Rights Movement and the Hippie Counterculture. While the Antiwar Movement aimed for a better, peaceful world as Baby Boomers were the first to live under the threat of the hydrogen bomb, the Civil Rights Movement strived to settle the matter of discrimination and race equality for the minorities; the Hippie Counterculture challenged social norms, questioned the authority and brought about a new way of life. During each series of events, Baby Boomers gradually shaped their visions and ideas about the world and their own country, which in turn helped shaping the United States the country as of today. Among novels and fictions reflecting this unique generation, The Drifters by James A. Michener is a powerful illustration of the Baby Boomers’ ideas, beliefs and ways of life. Studying the novel will offer a closer as well as distinctive look into some common traits of the people belonging to the Baby Boom Generation.